2022
DOI: 10.1111/tmi.13824
|View full text |Cite
|
Sign up to set email alerts
|

Level of adherence to anti‐tubercular treatment among drug‐sensitive tuberculosis patients on a newly introduced daily dose regimen in South India: A cross‐sectional study

Abstract: Introduction Tuberculosis (TB) patients on the National Tuberculosis Elimination Program (NTEP) treatment protocol receive daily doses without health professional‐supervised drug intake as during the previous directly observed treatment short‐course (DOTS) regimen. We aimed to measure the level of adherence to anti‐tubercular treatment (ATT) and the reasons for non‐adherence among drug‐sensitive TB patients on a daily‐dose regimen in South India. Methods A cross‐sectional study was conducted among TB patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…However, measuring adherence in routine care is difficult [ 171 , 172 ]. Use of novel and accurate approaches for detecting nonadherence, like urine drug metabolite testing [ 87 , 173 ], may facilitate early identification of people at risk for poor outcomes, so they can be given additional support. Medication adverse effects contributed to loss to follow-up across numerous studies for people with drug-susceptible TB (with up to 42% to 47% of people who stopped therapy doing so due to adverse effects [ 92 , 113 , 115 ]) and drug-resistant TB (with up to 75% of patients who stopped therapy doing so due to adverse effects [ 143 ]).…”
Section: Discussionmentioning
confidence: 99%
“…However, measuring adherence in routine care is difficult [ 171 , 172 ]. Use of novel and accurate approaches for detecting nonadherence, like urine drug metabolite testing [ 87 , 173 ], may facilitate early identification of people at risk for poor outcomes, so they can be given additional support. Medication adverse effects contributed to loss to follow-up across numerous studies for people with drug-susceptible TB (with up to 42% to 47% of people who stopped therapy doing so due to adverse effects [ 92 , 113 , 115 ]) and drug-resistant TB (with up to 75% of patients who stopped therapy doing so due to adverse effects [ 143 ]).…”
Section: Discussionmentioning
confidence: 99%
“…However, measuring TB medication adherence in routine care is challenging, with recent studies from India showing that 99DOTS (a digital adherence technology used in the NTEP) and patient self-report have suboptimal accuracy [182][183][184]. Use of novel approaches for detecting nonadherence, such as urine isoniazid testing [29,185], may facilitate early identification of patients at risk for poor outcomes, so that they can be provided with additional support. A recent study in India found that negative urine isoniazid test results…”
Section: Findings Specific To Each Care Cascade Gapmentioning
confidence: 99%
“…The standard antitubercular treatment (ATT) regimen for pulmonary tuberculosis (PTB) in India includes isoniazid, rifampicin (R), ethambutol, and pyrazinamide for the first 2 months, followed by isoniazid, rifampicin, and ethambutol for the next 4 months. Lengthy duration and adverse effects that affect drug compliance may contribute to unfavorable outcomes [ 1 ] and delay in achieving World Health Organization End TB Strategy targets. Hence, there is need for modification of existing drug regimens to achieve early bacteriologic conversion and to reduce ATT-induced toxicity.…”
mentioning
confidence: 99%